Choice of handedness and automated suturing for anthropomorphic dual-arm surgical robots. Issue 8 (October 2015) - Ding, Jienan; Simaan, Nabil
SUMMARY Laparoscopic and Single Port Access Surgery (SPAS) present unique dexterity challenges related to dual-arm operations in confined spaces and tele-manipulation of highly dexterous surgical slaves. In an effort to reduce tele-manipulation burden, new paradigms for semi-automating surgical tasks are needed. This paper presents a new minimal constraint suturing and automated choice of handedness for anthropomorphic dual-arm robots. The automated choice of handedness supports surgeons during tele-manipulation of complex robotic slaves where dexterity and workspace constraints are difficult to learn. This criterion is also used to support automated dual-arm rendezvous for quicker suture exchange during dual-arm suturing. The minimal constraint algorithm presented in this paper allows surgeons to operate within a shared-control tele-manipulation framework whereby the surgeon controls the needle insertion speed and the robot controls the needle orientation while respecting a minimalistic set of tissue constraints. This framework is evaluated on a novel insertable robotic end-effectors platform for SPAS. A simulation study demonstrates the effectiveness of the automated choice of handedness criterion through a study of dexterity limitations of each arm. Additional simulations show the proposed algorithm for automated rendezvous and suture exchange.